Anti-sunnah movement and its impact on the Muslim ummah - Zulkifli Mohd (International Islamic University Malaysia, 1995)
This study is and attempt to observe the existence of anti-Sunnah movement in the Islamic history. It tries to analyze the stand of anti-Sunnah group, as well as their polemics against the authority and authenticity of Sunnah. This study comprised five chapters. The first chapter provides a general overview of the study including a brief introductionk review of some literatures used in the studyk, scope of study, significance of the research and the methodology of research applied by the writers in completing his work. The second chapter contains the theoretical discussion of the concept of sunnah in Islam. In this chapter a deliberate attempt is made to develop a theoretical framework fo the entire study. It gives detailed background of the concept of Sunnah including the meaning of Hadith and Sunnah regarding the views of the Muhaddithun, the Usuliyyun and the "Fuqaha', and the categories of Sunnah. This has been followed by the discussion of the authority of Sunnaqgh as a legal source, and its role in relation to the Qur'an. Chapter three of this study deals with the historical ackkground of anti-Sunnah movement and its development in the Islamic era. The materials provided in this chapter constitute the background of anti-Sunnah movement prevailed in the early centuries of Islamic history, particularly in the second century of Hijrah. It also states the development of this movement in the following centuries, particularly in our recent century. Chapter four is taken up byh a discussion of some meterials relating to the stand of anti-Sunnah movement. The central focus of this chapter is to give an exposure to the two eminent leaders of anti-Sunnah movement in the recent century. Rashad Khalifa of th United States of America and Kassim Ahmad of Malaysia, regarding their stand on Sunnah. This chapter also provides and answer to the stand of anti-Sunnah movement. Chapter five, the concluding chapter, tried to analyze the impact of anti-Sunnah movement on the Muslim Ummah, particularly on th eMuslims in Malaysia. This chapter also remarks a general summary and brief observation to the whole works of the study.